Hydrothermally derived hydrochar from waste sawdust for solar vapor generation - Wong, Min Jin Karen; Wang, Zhipeng; Bih Lii Chua; Willey Y. H. Liew; Gan Jet Hong Melvin (Wiley Online Library, 2024)
Herein, hydrochar is derived from abundant and low-cost waste sawdust using hydrothermal carbonization in distilled water with a series of temperatures (150, 200, and 250 °C) and time (2 and 3 h), where the hydrochar characteristics are evaluated toward its application as a solar absorber. The hydrochar-based solar absorber is fabricated and tested using outdoor solar vapor generation under direct solar radiation with an average solar intensity of 1.26 kW m−2. The solar absorber incorporated with hydrochar is derived at 250 °C for 3 h and displays the best average efficiency (71.35 ± 0.90%) and evaporation rate (1.30 ± 0.04 kg m−2 h−1). The collected clean water salinity (below 300 ppm) and pH (6.72–7.23) from the solar absorber is within the safe drinking water limit by the World Health Organization. Therefore, the hydrochar-based solar absorber can be used to generate clean water from seawater desalination using solar vapor generation.